Rating tools for shariah compliant hospitality and services: landscape design stage - Othman, Rashidi; Abu Kasim, Siti Zubaidah; Hashim, Khairusy Syakirin Has-Yun; Mohd Latiff, Nur Hanie; Mahamod, Lukman Hakim (American Scientific Publishers, 2015)
Currently, tourism sector has become the most dynamic factor to Malaysian services economic growth. The existence of Shariah compliant hospitality and services will be an added value in promoting Malaysia as Muslim friendly Tourism Hub. Specifically to the international tourist such as Middle East, West Asian and other Islamic countries. Shariah compliant concept is not restricted to only halal food and hygienic accommodation. Utterly, hoteliers have focused mainly on the beverages and accommodation qualifications factors in order to fulfill the Shariah compliant concept. The built environment facilities such as landscape features provided at these premises is also the main contributor to the Shariah compliant philosophy. The guidelines for Shariah compliant services and hospitality is still ambiguous among the hoteliers, tourists and its’ stakeholders. Realizing that there is no standard guideline and rating tools that can audit Shariah compliant landscape design at Malaysian Tourism Accommodation Premises (TAP) therefore, the aim of this paper is to highlight the significance of rating tools and audit system for landscape design and its facilities provided at Tourism Accommodation Premises (TAP). This effort is a mean to promote Shariah compliant hospitality and services among hoteliers and tourists. With this gap in view, it is hope that this research will provide the guidelines for Shariah compliant landscape design to designers, hoteliers and all stakeholders at TAP.